Unloading-creep test and long-term strength study of different initial conditions of limestone. Issue 2 (October 2021) - Xu, Xiaoliang; Zhang, Cheng; Yin, Sijie; Huang, Tianzhu; Wang, Lehua
Abstract: The high-slope limestone on the right bank of the Wudongde Hydropower Station dam site was considered as a research object to conduct a triaxial unloading-creep test, and then to analyze in detail the limestone's creep characteristics under different test conditions so as to investigate the limestone's unloading-creep mechanical properties under different unloading rates and initial stress levels. The results show that the faster the unloading rate, the greater the limestone's axial and lateral creep rate when under the same stress state. Furthermore, the lateral creep rate is greater than the axial creep rate, indicating an apparent lateral expansion. When the unloading rate is constant, the stress difference has a significant impact on the limestone. The specific manifestation is that the greater the deviator stress, the more pronounced the limestone creep phenomenon, and the rock sample is prone to damage. The steady-state rate intersection method is employed to determine the limestone's long-term strength, and the λ parameter is introduced to reduce the influence of the axial and lateral strain increments on the long-term strength determination during the unloading process.